2019
DOI: 10.3390/md17020135
|View full text |Cite
|
Sign up to set email alerts
|

Amino Acid Composition, Antioxidant, and Cytoprotective Effect of Blue Mussel (Mytilus edulis) Hydrolysate through the Inhibition of Caspase-3 Activation in Oxidative Stress-Mediated Endothelial Cell Injury

Abstract: Enhanced oxidative stress plays a central role in promoting endothelial dysfunction, leading to the development of atherosclerosis. In this study, we investigated the protective effects of the hydrolysates derived from blue mussel (Mytilus edulis) against H2O2-mediated oxidative injury in human umbilical vein endothelial cells (HUVECs). The blue mussel hydrolysates were prepared by enzymatic hydrolysis with eight proteases, and blue mussel-α-chymotrypsin hydrolysate (BMCH) showed the highest antioxidant activi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
25
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 36 publications
(30 citation statements)
references
References 52 publications
5
25
0
Order By: Relevance
“…As described in Section 4.2 and Section 4.3 , some cell models and animal experiments have shown that PAs have a significant protective effect on cells under oxidative stress. PAs have the effects of anti-fatigue, improving memory and vascular health [ 268 ], protecting the liver [ 269 , 270 ], reducing ROS-related pro-inflammatory reactions [ 221 , 271 ] and preventing atherosclerosis [ 272 , 273 ], which provides a basis for their application in nutritious foods, functional foods, dietary supplements and other fields [ 274 ]. Cuttlefish-purified peptides can obviously inhibit the oxidation process of linoleic acid, effectively protect the DNA damage induced by • OH radicals, and have no toxic effect to cells at higher concentrations [ 159 ].…”
Section: Potential Application Of Food-derived Pasmentioning
confidence: 99%
“…As described in Section 4.2 and Section 4.3 , some cell models and animal experiments have shown that PAs have a significant protective effect on cells under oxidative stress. PAs have the effects of anti-fatigue, improving memory and vascular health [ 268 ], protecting the liver [ 269 , 270 ], reducing ROS-related pro-inflammatory reactions [ 221 , 271 ] and preventing atherosclerosis [ 272 , 273 ], which provides a basis for their application in nutritious foods, functional foods, dietary supplements and other fields [ 274 ]. Cuttlefish-purified peptides can obviously inhibit the oxidation process of linoleic acid, effectively protect the DNA damage induced by • OH radicals, and have no toxic effect to cells at higher concentrations [ 159 ].…”
Section: Potential Application Of Food-derived Pasmentioning
confidence: 99%
“…The importance of nutrition and the benefits of dietary supplements to health promotion and disease prevention have been documented increasingly in specific studies [ 14 , 50 ]. Many studies have shown that antioxidant peptides could effectively enhance the oxidative stress resistance of organisms by neutralizing free radicals, prohibiting oxidative chain reactions, and regulating multiple stress-responsive pathways and gene expressions [ 51 , 52 , 53 ]. Combined with the results of the present studies, peptides as an important class of antioxidants are capable of providing protective effects against oxidative stress and fat accumulation, which have the potential to be used in nutraceutical and functional foods for disease prevention.…”
Section: Resultsmentioning
confidence: 99%
“…A peptide Hydrolysate derived from blue mussel (Mytilus edulis) and designated BMCH has also been reported to exhibit antioxidant activities as indicated by DPPH radical scavenging (IC 50 0.35 mg/ml) and ABTS+ radical scavenging activity (117 µM TE/Mg sample) [52]. BMCH also showed a protective effect against H 2 O 2 -mediated oxidative injury in human umbilical vein endothelial cells (HUVECs) by increasing cellular antioxidant capacities, including increasing levels of catalase, glutathione (GSH), glutathione peroxidase and superoxide dismutase, thus indicating that BMCH may be useful in in protecting against endothelial dysfunction and related diseases [56].…”
Section: Peptides With Antioxidant Activitymentioning
confidence: 99%
“…Lower molecular weight peptides possess stronger antioxidant activity compared to peptides with higher molecular weight this may be due to improved permeability and/or better contact ability with membrane lipids lower molecular weight peptides [32,56] addition, the presence of histidine and aromatic amino acids in the peptide structure may be an advantage as these amino acids can easily donate protons to electron-deficient radicals while maintaining their stability via resonance structures [32,58].…”
Section: Peptides With Antioxidant Activitymentioning
confidence: 99%